Thinking strategically the competitive edge in business, politics, and everyday life - Dixit, Avinash K.; Nalebuff, Barry 1958- (W.W. Norton & Company, 1993)
A major bestseller in Japan, Financial Times Top Ten book of the year, Book-of-the-Month Club bestseller, and required reading at the best business schools, Thinking Strategically is a crash course in outmaneuvering any rival. This entertaining guide builds on scores of case studies taken from business, sports, the movies, politics, and gambling. It outlines the basics of good strategy making and then shows how you can apply them in any area of your life.